A fruit extract of Styphnolobium japonicum (L.) counteracts oxidative stress and mediates neuroprotection in Caenorhabditis elegans - Thabit, Sara; Handoussa, Heba; ElSayed, Nesrine S.; Breitinger, Hans-Georg; Breitinger, Ulrike; Wink, Michael (BMC complementary medicine and therapies, 2023)
Background: Despite its widespread uses in Chinese and European medicine, Styphnolobium japonicum (Chinese scholar tree, formerly Sophora japonicum) has not been extensively investigated for its potential to protect against neurodegenerative processes and to promote resistance to oxidative stress. In this study, we evaluated the neuroprotective activities of a hydroalcoholic extract from Chinese scholar tree fruits that could be possibly linked to its antioxidant properties using Caenorhabditis elegans as a well-established in vivo model. Methods: Survival rate in mutant daf-16 and skn-1 worms, stressed by the pro-oxidant juglone and treated with the extract, was tested. Localization of the transcription factors SKN-1 and DAF-16, and expression of gst-4 were measured. For evaluation of neuroprotective effects, formation of polyglutamine (polyQ40) clusters, α-synuclein aggregates, loss of amphid sensilla (ASH) neuronal function, and amyloid β (Aβ) accumulation (as markers for Huntington’s, Parkinson’s, and Alzheimer’s) was examined. Results: The extract, which contains substantial amounts of phenolic phytochemicals, showed an increase in the survival rate of worms challenged with juglone in daf-16 mutants but not in skn-1 mutants. The transcription factor SKN-1 was activated by the extract, while DAF-16 was not affected. Upon application of the extract, a significant decline in GST-4 levels, polyQ40 cluster formation, number of lost ASH sensory neurons, α-synuclein aggregation, and paralysis resulting from Aβ accumulation was observed. Conclusions: Styphnolobium japonicum fruit extract activated the SKN-1/Nrf2 pathway, resulting in oxidative stress resistance. It revealed promising pharmacological activities towards treatment of Huntington’s, Parkinson’s, and Alzheimer’s diseases. Polyphenolics from Styphnolobium japonicum may be a promising route towards treatment of CNS disorders, but need to be tested in other in vivo systems.
Gesehen am 27.11.2023